Emancipating New York : The Politics of Slavery and Freedom, 1777-1827 - Gellman, David N. (Book collections on Project MUSE., 2008)
An innovative blend of cultural and political history, Emancipating New York is the most complete study to date of the abolition of slavery in New York state. Focusing on public opinion, David N. Gellman shows New Yorkers engaged in vigorous debates and determined activism during the final decades of the eighteenth century as they grappled with the possibility of freeing the state's black population. The gradual emancipation that began in New York in 1799 helped move an entire region of the country toward a historically rare slaveless democracy, creating a wedge in the United States that would.